Evaluating ocean alkalinity enhancement as a carbon dioxide removal strategy in the North Sea - F. Liu; U. Daewel; J. Kossack; K. T. Demir; H. Thomas; H. Thomas; C. Schrum; C. Schrum (Biogeosciences)
Ocean alkalinity enhancement (OAE) is a climate mitigation strategy aimed at increasing the ocean's capacity to absorb and store atmospheric CO2. The effect of OAE depends significantly on local physical and biogeochemical conditions, underscoring the importance of selecting optimal locations for alkalinity addition. Using a regional coupled physical-biogeochemical-carbon model, we examine OAE responses in the North Sea, including CO2 uptake potential, enhanced carbon storage and cross-shelf export, and the associated changes in the carbonate chemistry. Alkalinity is continuously added as a surface flux in three distinct regions of the North Sea. Our simulations show that the Norwegian Trench and the Skagerrak serve as sinks for added alkalinity, reducing its interaction with the atmosphere. Alkalinity addition along shallow eastern coasts results in a higher CO2 uptake efficiency (∼0.79 mol CO2 uptake per mol alkalinity addition) than offshore addition in ship-accessible areas (∼0.66 mol CO2 uptake per mol alkalinity addition) as offshore alkalinity is more susceptible to deep-ocean loss. Long-term carbon storage, measured by excess carbon accumulation in deep ocean and cross-shelf export below permanent pycnoclines, is similar across the three scenarios and accounts for less than 10 % of total excess CO2 uptake. The smallest changes in pH occur when alkalinity is added offshore with effects nearly an order of magnitude lower than alkalinity addition in the shallow German Exclusive Economic Zone where pH increases from 8.1 to 8.4. The model's resolution (∼4.5 km in coastal areas) limits its ability to capture rapid, localized carbonate responses, leading to a nearly 10-fold underestimation of chemical perturbations. Thus, finer-scale models are needed to accurately assess near-source alkalinity impacts.